Spousal Coping Strategies in the Shadow of Terrorism - Shechory-Bitton, Mally (Journal of interpersonal violence, 2021)
The present study focuses on spousal differences in reaction to ongoing exposure to terror and security threats. Sixty-eight married couples with children living in a region exposed to ongoing security threats were evaluated. All participants completed questionnaires on objective exposure (number of incidents) and subjective exposure (sense of fear) to terrorism and security threats, posttraumatic stress disorder (PTSD) symptoms, and their coping strategies with this ongoing exposure. Mothers reported higher levels of fear and PTSD symptoms, although their objective levels of exposure did not differ from those of their husbands. Similarities were found in coping strategies adopted by mothers and fathers to cope with life in the shadow of terrorism. Both mothers and fathers integrated emotion- and problem-focused coping strategies, with greater use of the latter. These similarities partially contradict research findings suggesting gender differences in coping with exposure to security threats. The results support the need for further research into investigating the role of dyadic coping in the context of prolonged exposure to security threats.